Beyond Structural Change: A Cultural Interpretation of School Principals’ “Burnout National” Survey by ANP–LUMSA - Grazia Angeloni (European Scientific Journal, ESJ, 2026)
The 2025 ANP–LUMSA national survey provides robust empirical evidence of widespread occupational stress among Italian school principals, characterized by high cognitive and emotional demands, excessive workloads, and significant risks of burnout. While these findings are empirically sound and methodologically rigorous, their interpretation cannot be confined to a purely structural or organizational framework. This article argues that the explanatory power of the survey is substantially enhanced when read through a culturalist lens, distinguishing between episodic organizational changes or structural reengineering and deeper processes of cultural transformation in the anthropological sense. From this perspective, principals’ burnout emerges not only as a consequence of excessive demands and insufficient resources but as the outcome of a progressive delegitimization of the leadership role, weakened institutional trust, and governance cultures oriented toward control rather than support. The paper proposes that meaningful improvement cannot be achieved solely through middle management expansion or administrative reinforcement, as suggested by the survey respondents, but requires a reconfiguration of the ethical, symbolic, and relational foundations of school leadership. Such a shift redefines principals’ wellbeing as a collective institutional responsibility and calls for policy responses centered on role recognition, professional dignity, and trust-based educational governance. By integrating empirical evidence with cultural analysis, this study tries to contribute to a more comprehensive understanding of leadership burnout and offers a theoretically grounded foundation for policy approaches capable of producing not merely change, but genuine transformation in educational systems.